Sensitization in Heart Transplantation: Emerging Knowledge. Issue 12 (19th March 2019) - Colvin, Monica M.; Cook, Jennifer L.; Chang, Patricia P.; Hsu, Daphne T.; Kiernan, Michael S.; Kobashigawa, Jon A.; Lindenfeld, JoAnn; Masri, S. Carolina; Miller, Dylan V.; Rodriguez, E. Rene; Tyan, Dolly B.; Zeevi, Adriana
Abstract : Sensitization, defined as the presence of circulating antibodies, presents challenges for heart transplant recipients and physicians. When present, sensitization can limit a transplantation candidate's access to organs, prolong wait time, and, in some cases, exclude the candidate from heart transplantation altogether. The management of sensitization is not yet standardized, and current therapies have not yielded consistent results. Although current strategies involve antibody suppression and removal with intravenous immunoglobulin, plasmapheresis, and antibody therapy, newer strategies with more specific targets are being investigated.